An estimate of the value of lost load for Ireland - Eimear Leahy; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2010)
This paper estimates the value of short term lost load in the all island electricity market which includes the Republic of Ireland and Northern Ireland. The value of lost load, also known as the value of security of electricity supply, is inferred using a production function approach. Detailed electricity use data for the Republic of Ireland allows us to estimate the value of lost load by time of day, time of week and type of user. We find that the value of lost load is highest in the residential sector in both the Republic of Ireland and Northern Ireland. Our results can be used to advise policy decisions in the case of supply outages and to encourage optimum supply security. In the context of this study short term is taken to be a matter of hours rather than days or weeks.
Keywords: 330; value of lost load; Ireland; Elektrizitätswirtschaft; Energieversorgung; Irland